2010
DOI: 10.1111/j.1743-6109.2010.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectations Prior to Coloplast Titan Penile Prosthesis Implant Predicts Postoperative Satisfaction

Abstract: Introduction Managing and understanding expectations of patients prior to inflatable penile prosthesis (IPP) surgery is a critical. Clinicians vary in the way they explain the operation, and patients have varied expectations prior to surgery. Aims The goal is to understand the role that preoperative counseling and patients’ realistic understanding of IPP surgery play in determining postoperative satisfaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Partners' attitudes may play a role [17] and patient expectations can have a great impact [18]. Poor outcomes requiring explantation and secondary procedures affected responses.…”
Section: Discussionmentioning
confidence: 99%
“…Partners' attitudes may play a role [17] and patient expectations can have a great impact [18]. Poor outcomes requiring explantation and secondary procedures affected responses.…”
Section: Discussionmentioning
confidence: 99%
“…14 Generally, after PPI dissatisfaction is due to a perceived loss of penile length, 15 postoperative pain and difficulty in using the device. 7 Recent series in the literature have shown that penile prosthesis are used by the large majority of patients undergoing PPI (89-97%). 4,16 In some cases, however, patients do not accept their new sexuality and they may even decide for the removal of the device.…”
Section: Discussionmentioning
confidence: 99%
“…This communication gap may produce unrealistic expectations in men and partners, causing variable degrees of postoperative dissatisfaction. 7 Porena et al 18 were the first to address the issue of the couple's satisfaction after PPI, concluding that the degree of satisfaction is the best indicator to verify the effectiveness of therapy. A recent study highlighted the key role of female partners' sexual function in couples' satisfaction rates after PPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies published until now which evaluated each type of prosthesis independently as regards the satisfaction of the patient, the partner and the surgeon. Similarly, studies have been conducted to assess both types of prostheses independently in very specific scenarios such as to evaluate new developments and technical advances of each of the prostheses, or to compare their effectiveness in special clinical situations such as for concomitant DE and Peyronie's disease treatment 379101112…”
Section: Introductionmentioning
confidence: 99%